Investigating the effect of spatiotemporal, wind speed and wind direction on precipitation magnitudes within an urban area - Hayder Algretawee; Scott Rayburg; Melissa Neave (Water Science and Technology, 2023)
Some documented precipitation changes are associated with the hydrological cycle, including changes in the magnitude of precipitation. Studying the effect of spatial, temporal, wind speed and wind direction on precipitation magnitude at specified points within Melbourne city – Australia could reveal how they affect precipitation magnitudes. To achieve this aim, a long rainy day was adopted to record the measurements at different places and times throughout the day and night. The study method involved measuring wind speed and direction at every measuring point by using a hand-held device, while precipitation values were recorded using the nearest ground weather station. The study revealed precipitation magnitudes at night were higher than during daylight hours. On the other hand, fast winds increase precipitation magnitude, and wind direction has an effect on precipitation either increasing or decreasing depending on upwind and leeward sides, respectively. Respective to temporal parameters, precipitation magnitudes at night showed the highest. Wind speed directly affects precipitation values but the direction has a moderate effect on precipitation. Generally, spatiotemporal, wind speed and direction have a distinct effect on precipitation with a small time scale. HIGHLIGHTS A new methodology was used by selecting continuous storms which extended more than 20 h.; A long rainy day was adopted to study the effect of spatial, temporal parameters and some weather features on precipitation magnitudes at specified points.; Spatiotemporal, wind speed and direction have a distinct effect on precipitation around the greening areas within an urban area with a small time scale.;